Film Sebagai Pemankin Pembangunan Peradaban Melayu-Islam Modern - Rahimin Affandi Abd Rahim; Abdullah Yusof; Nor Adina Abdul Kadir (Sharia and Law Faculty, 2012)
This article discusses on the genre of Islamic film as a visual creative innovation that had played a significant role in the society. Film can be regarded as a effective platform in distributing an Islamic idealism propose by the Malaysian and Indonesian’s film director. Obviously the inclusion of Islamic point of view for the development of Malay-Muslim civilization can be done through the medium of film. Based on such background setting, the article had touched on several issues pertaining to the issues of contemporary Islamic problem and collective role needed to be played by both of Islamic scholar and film director. It is suggested that a mutual understanding between ulamak and film director will contributed toward the betterment of Islamic ummah at the modern time.